HUBUNGAN PENGETAHUAN GIZI DENGAN SIKAP MENGKONSUMSI MAKANAN SEHAT SISWA SMK - Syafira Salsabilla (UNIVERSITAS SARJANAWIYATA TAMANSISWA, 2017)
The objectives of this study are to know the correlation betweennutrition knowledge toward attitude of consuming health foods, nutrition knowledge, and attitude of consuming health foods. The type of this study was a ex-post fact. The sample was taken by using Isaac and Michael.Data collection technique used questionnaire. The validity test used Product Moment and reliability used Cronbach Alpha.Data analysis technique used descriptive analysis and hypothesis testing by using Product Moment that was started by normality and linearity test. This study shows that: there was a positive and significant correlationbetweennutrition knowledge toward attitude of consuming health foods and nutrition knowledgegave a contribution toward attitude of consuming health foods40.4% while 59.6% was correlationd by other factors,nutrition knowledge was in fair category, andattitude of consuming health foods was in fair category.Â Key words: nutrition knowledge, attitude of consuming health foods